Neural correlates of attentional and executive processing in middle-age fencers - Taddei, F.; Bultrini, A.; Spinelli, D.; Di Russo, F. (Medicine & Science in Sports & Exercise, 2012)
Purpose: Open-skill sports require high levels of visual attention and fast and flexible decision making and action execution. We evaluated whether these sports may counteract the well-known age-related declines in executive processing.